THE IMPACT OF ISLAMIC VALUE ON PRODUCTIVITY IN AN ISLAMIC HIGHER EDUCATION INSTITUTION - Mohammad Rosli, Nurul Ain; Md Dahlal, Norazilawati; Mohd Salleh, Hamzah; Ahmad, Anis Najiha (AR-RĀ’IQ, 2023)
The Islamic higher education paradigm has evolved from a traditional approach focusing solely on theology and religious studies to a Muslim-driven need for high-quality education that combines wide-ranging knowledge with an infusion of Islamic viewpoints. While Islam emphasizes and measures values, worker’s productivity in Islamic higher educational institutions still primarily relies on conventional productivity methods that prioritize Western perspectives and values, rather than Islamic ones. However, Islamic values such as taqwa, shukr, sabr, itqan, ihsan, and ikhlas can potentially improve worker efficiency and productivity. Purpose of the study: This research focuses on assessing the impact of the Islamic values on worker’s productivity in an Islamic higher education institution. Methodology: Using a quantitative method, data was collected through questionnaires distributed to workers at the International Islamic University Malaysia, Gombak. Main Findings: Results from 63 respondents revealed a mixed impact of Islamic values on worker productivity. This finding underscores the need for further research to delve deeper into the nuanced relationship between Islamic values and productivity in the workplace. Novelty: Many studies in organizational behaviour may overlook or downplay the role of religious values in shaping attitudes and behaviours in the workplace. Despite Malaysia's infusion of Islamic values into civil service policies, there remains a lack of understanding among Muslim employees regarding their practical application in the workplace. This study integrates Islamic perspectives by examining Islamic values such as taqwa, shukr, sabr, itqan, ihsan, and ikhlas and their potential influence on worker productivity. This integration adds a unique dimension to the study's findings.